SURGICAL TREATMENT OF EAR HAEMATOMA IN DOGS - Mohsin Abdul Jalil Falih (Basrah Journal of Veterinary Research)
The was conducted on 15 dogs of either sex and of different breed presented at my clinic (canine clinic* during a period of sex months. Their ages were ranging between 2-3 years. The dogs showing unilateral or bilateral swollen ear that is Haematoma. The surgical treatment was done by making a longitudinal incision on in entire length of haematoma. After draining the blood or serum, cleaning the debris. Haematoma pocket flushed with saline or week tincture iodine. Horizontal interrupted materess suture placed parallel to the incision, the pinna was dressed with antiseptic then bandaged with compression bandage to keeping the ear in erect position. The suture removed after 9-10 days post operation. Bandaging will continue to 6 more days till the operated ear return to its normal condition.